GST- A Journey of continuous reforms in the Indian Indirect Taxation system: - (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The implementation of the Goods and Services Tax (GST) in India is a remarkable move in thefield of indirect tax reforms. With the amalgamation of the majority of Central and State taxes into anexclusive single tax, GST eliminates the detrimental effects of cascading and double taxation and pavesthe way for a single common national market. Introduction of GST makes Indian products competitive bothin the domestic and international markets owing to the full neutralization of input taxes across the valuechain of production and distribution. Being transparent, it is easier to administer a shift from a ratherinformal to formal economy. This paper presents an overview of the journey of GST implementation inIndia and examines its effect on the Indian economy.